Kedudukan dan Peran Manusia dalam Alam: Tanggapan atas Kritik Al Gore terhadap Arne Naess - Barnabas Ohoiwutun (Jurnal Ledalero, 2021)
This articleaims to respond Al Gore’s critics onArne Naess’ concept of deep ecology. ForAl Gore, deep ecology of ArneNaesshas reduced the position and the role of human being in nature. The reason is becauseNaess’s deep ecologyis assumed to see human being as the source of destruction on earth and alien which is not part of nature; it grasps man as creature without ability to think and to have free will; and it has no solution for current ecological crisis. Naess, in constrast, comprehends human beings as good in himself, part of nature, and a unique creature. Because of this uniqueness,human being has responsibility to protect and to preserve nature.Thus, although they have differences, both deep ecology of Naess and the ecology of Al Gore havemany similarities. These similarities can be used ascontribution to any effort to save the earth today.Key words: ekologi dalam, menusia, alam, antroposentrisme, ekosentrisme